Magnetic-reconnection-driven Turbulence and Turbulent Reconnection Acceleration - Shi-Min Liang; Jian-Fu Zhang; Na-Na Gao; Hua-Ping Xiao (The Astrophysical Journal, 2023)
This paper employs an MHD-PIC method to perform numerical simulations of magnetic-reconnection-driven turbulence and turbulent reconnection acceleration of particles. Focusing on the dynamics of the magnetic reconnection, the properties of self-driven turbulence, and the behavior of particle acceleration, we find the following: (1) When reaching a statistically steady state of the self-driven turbulence, the magnetic energy is almost released by 50%, while the kinetic energy of the fluid increases by no more than 15%. (2) The properties of reconnection-driven turbulence are more complex than the traditional turbulence driven by an external force. (3) The strong magnetic field tends to enhance the turbulent reconnection efficiency to accelerate particles more efficiently, resulting in a hard spectral energy distribution. Our study provides a particular perspective on understanding turbulence properties and turbulent-reconnection-accelerated particles.